A polyvinyl butyral-based light control film and a method for preparing the same

CN122902126APending Publication Date: 2026-10-13ZHEJIANG DECENT PLASTIC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611390500.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0004]但实际中遇到了较多的工程问题:第一,PVB胶膜需要高温高压与玻璃粘结在一起,高温高压夹胶工艺需要较高的温度(130-140℃),而聚合物分散液晶(PDLC)无法耐受长时间的高温

Benefits of technology

[0039]1.本发明聚乙烯醇缩丁醛基调光膜,以增塑剂含量不同的双层结构PVB胶膜为外层粘接与承载基体制备聚乙烯醇缩丁醛基调光膜,压合装配在夹层玻璃时,PVB胶膜高增塑剂含量层柔性良好,易热熔流动性,直接接触玻璃,可在较低温度下施加压力发生充分流动与玻璃紧密粘接,防止气泡缺陷,避免高温压合损伤液晶层。PVB胶膜低增塑层热稳定,避免滑移损伤,有效保护内部的PDLC功能层。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122902126A_ABST
    Figure CN122902126A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of intelligent dimming film, and provides a polyvinyl butyral-based dimming film and a preparation method thereof.The dimming film comprises, from top to bottom, a first adhesive film, a first conductive film, a PDLC functional layer, a second conductive film, and a second adhesive film.The first adhesive film and the second adhesive film are both double-layer PVB adhesive films, which are composed of a high plasticizer content layer and a low plasticizer content layer.When being assembled in laminated glass, the high plasticizer content layer of the PVB adhesive film has good flexibility, directly contacts the glass, can be subjected to pressure at a relatively low temperature to flow sufficiently and adhere to the glass tightly, prevents bubble defects, and avoids damage to the liquid crystal layer caused by high-temperature assembly.The present application solves the problem of slippage and misplacement of the PDLC film and the PVB film when being assembled in laminated glass at high temperature.The present application is suitable for continuous industrial production, has stable process, and has no warping deformation in layer compounding, thereby laying a technical foundation for replacing intermittent high-temperature hot pressing and stably producing dimming films for automobile glass and building glass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of intelligent dimming film technology, and relates to a polymer dispersed liquid crystal (PDLC) dimming film that can be used in automotive glass and architectural glass, particularly a polyvinyl butyral-based dimming film and its preparation method. Background Technology

[0002] A dimming film is a smart material that controls light transmittance through an electric field. Polymer-dispersed liquid crystal (PDLC) dimming films are formed by dispersing micron-sized liquid crystal droplets in a polymer and encapsulating them between two conductive films. The random dispersion of the liquid crystal particles causes the dimming film to fog up and block light; when an electric field is applied through the conductive layer, the liquid crystal particles align in an orderly manner, and the dimming film instantly becomes transparent. Dimming films encapsulated in glass can create electronic curtains, allowing the glass to switch between transparent and frosted states via voltage control. In recent years, the application of dimming films in automotive glass, high-speed rail windows, architectural glass, and smart windows has developed rapidly. Currently, the most mature dimming films mainly use indium tin oxide (ITO) deposited on a PET base film using magnetron sputtering technology to form an ITO-PET conductive film. Polymer-dispersed liquid crystal (PDLC) is coated on the ITO conductive surface of the conductive film, and the PDLC is encapsulated between the two conductive films to form the dimming film.

[0003] PET base film is heat-resistant and can withstand the high-temperature annealing of ITO coatings. Its low thermal shrinkage and high tensile strength prevent excessive shrinkage from causing the ITO layer to become brittle. PVB (polyvinyl butyral) film, on the other hand, softens at high temperatures and has a high thermal shrinkage rate. Using it directly as a substrate for ITO magnetron sputtering can lead to cracks and peeling of the ITO layer, and a sharp deterioration in sheet resistance. Therefore, when used in automotive and architectural glass, dimming films are mainly laminated and embedded. The PDLC dimming film is sandwiched between PVB (polyvinyl butyral) films, layered in the order of "glass / PVB film / PDLC film / PVB film / glass," and laminated into dimming glass using a high-temperature, high-pressure lamination process.

[0004] However, several engineering problems were encountered in practice: First, the PVB film needs to be bonded to the glass under high temperature and pressure. This high-temperature, high-pressure lamination process requires high temperatures (130-140℃), which polymer-dispersed liquid crystals (PDLCs) cannot withstand prolonged high temperatures. If low-temperature lamination (100℃) is used, the PVB film's fluidity deteriorates, failing to fill the gaps and easily generating bubbles, affecting its adhesion to the glass. Second, the PDLC film and PVB film, based on PET, are independent films. During stacking, lamination, and bonding, relative slippage and misalignment are highly likely, leading to product scrap or performance degradation. Furthermore, alignment accuracy is difficult to guarantee, severely impacting production efficiency and yield. Third, the PET substrate of the PDLC film and the PVB film rely solely on physical bonding via hot pressing, resulting in defects such as interface separation, bubbles, fogging, and spots, affecting the optical quality of the switching glass. Additionally, separate procurement of PDLC and PVB films is required during glass lamination and encapsulation, adding an alignment process, complicating the process, increasing manufacturing costs, and lowering the yield.

[0005] To improve the bonding effect between the dimming film and glass, Chinese invention patent publication CN115257116B discloses a dimming component, its preparation method, and a vehicle. The dimming component includes a first light-transmitting plate, a first adhesive layer, a dimming film, a second adhesive layer, and a second light-transmitting plate stacked sequentially. A buffer layer is provided between the first adhesive layer and the dimming film, and / or between the second adhesive layer and the dimming film. By introducing the buffer layer, the flow temperature of the buffer layer is lower than that of the adhesive layer. During lamination processing, the buffer layer has good fluidity and can promptly fill the dimming film, avoiding bubble defects. However, the adhesive layer (PVB film) still requires high-temperature, long-term bonding. Chinese invention patent publication CN115816941B discloses a smart dynamic dimming laminated glass and its preparation method. Instead of using liquid crystal dimming, it uses inorganic rod-shaped nanoparticles, cesium-doped tungsten oxide, to prepare the dimming film. Its high-temperature resistance allows it to withstand the high temperatures of the lamination process when using PVB film. It only possesses electrochromic properties and does not have the function of liquid crystal fogging. Chinese invention patent publication number CN112379546B discloses a polymer disperse dye liquid crystal material, an electrochromic color-changing film and its preparation method. In order to avoid dye degradation during UV curing of the polymer disperse dye liquid crystal layer, a thermosetting adhesive (epoxy resin adhesive) is used to form the polymer disperse dye liquid crystal layer.

[0006] To address this, we developed a composite dimming film that can be directly used for dimming laminated glass. By pre-compositing the PVB film with the dimming film, we solve the problems of displacement, bubbles, and poor adhesion to the glass during lamination, and simplify the back-end assembly process. Summary of the Invention

[0007] In the preparation of automotive dimming glass, PDLC film and PVB (polyvinyl butyral) film are stacked in a "glass / PVB film / PDLC film / PVB film / glass" configuration and prepared using a high-temperature, high-pressure lamination process. This high-temperature lamination not only affects the stability of the liquid crystal and causes fogging, but also, because the PDLC film's substrate is PET, relative slippage easily occurs between the PET and PVB films during hot-press bonding, resulting in bubbling and a high product scrap rate. Therefore, this invention proposes a polyvinyl butyral-based dimming film and its preparation method. The core of this method is: using a double-layer PVB film as the outer bonding and carrier substrate, and pre-bonding an ITO-PET conductive film and a PVB film to form a composite conductive film, allowing the polymer-dispersed liquid crystal (PDLC) to be directly encapsulated between the two composite conductive films, forming an inseparable, integrated, multifunctional composite dimming film.

[0008] To achieve the aforementioned technical effects, the specific technical solution adopted by the present invention is as follows:

[0009] First, a polyvinyl butyral-based dimming film is provided, wherein the dimming film comprises, from top to bottom, a first adhesive film, a first conductive film, a PDLC functional layer, a second conductive film, and a second adhesive film;

[0010] Both the first and second films are double-layer PVB films, which consist of a high plasticizer content layer and a low plasticizer content layer; the high plasticizer content layer contains epoxy resin and maleic anhydride-grafted EVA.

[0011] Both the first conductive film and the second conductive film are PET-ITO conductive films;

[0012] The low plasticizer content layer of the first adhesive film is bonded to the PET layer of the first conductive film by an adhesive; the low plasticizer content layer of the second adhesive film is bonded to the PET layer of the second conductive film by an adhesive.

[0013] The adhesive used is either optical UV adhesive or transparent epoxy resin AB adhesive;

[0014] The PDLC functional layer is a polymer-dispersed liquid crystal layer with a thickness of 10-20 μm.

[0015] Conventional PVB films and dimming films require temperatures above 130°C to bond fully when laminated in glass. This temperature far exceeds the clearing point of liquid crystals, and prolonged high-temperature lamination can cause irreversible damage to the liquid crystal, increase haze, and severely affect encapsulation quality. Therefore, this invention pre-composites the PVB film with a conductive film to form a composite dimming film, which can be directly used for glass interlayer lamination, avoiding defects such as slippage and bubbles. Furthermore, it employs a double-layer PVB film with different plasticizer contents. When the dimming film is laminated and assembled into the glass, the high-plasticizer-content layer of the PVB film directly contacts the glass, allowing it to flow and bond tightly to the glass under pressure at a lower temperature, thus preventing damage to the liquid crystal layer during high-temperature lamination.

[0016] Preferably, the double-layer PVB film is obtained from PVB resins with different plasticizer contents in a double-layer co-extrusion casting line. Two extruders separately melt PVB resins with different plasticizer contents, which are then cast through a precision T-die, stacked, and bonded together. The film is then rapidly cooled and shaped using quench rollers.

[0017] Preferably, the plasticizer content in the low-plasticizer content layer of the double-layer PVB film is 20-30 wt% of PVB resin; the plasticizer content in the high-plasticizer content layer is 60-80 wt% of PVB resin. More preferably, the plasticizer is either dibutyl fumarate (DBF) or triethylene glycol diisooctanoate (3GO).

[0018] Preferably, the low plasticizer content layer of the double-layer PVB film uses PVB resin with a hydroxyl content of 18-20 wt%; the high plasticizer content layer uses PVB resin with a hydroxyl content of 12-15 wt%. The low hydroxyl content can reduce the accumulation of moisture, avoid the generation of bubbles during lamination, and lower the softening and melting temperature, thus balancing the flowability and adhesion of hot pressing.

[0019] Preferably, the high plasticizer content layer of the double-layer PVB film contains maleic anhydride-grafted EVA with a melting point of 70-90℃, accounting for 8-12 wt% of the PVB resin; and epoxy resin, accounting for 3-5 wt% of the PVB resin. The maleic anhydride-grafted EVA, in conjunction with the epoxy resin, introduces polar groups, improving the adhesion between the high plasticizer content layer of the PVB film and the glass, allowing the PVB film to flow at lower temperatures and fully penetrate and bond with the glass.

[0020] Optionally, the thickness of the double-layer PVB film is 0.38 mm. The thickness ratio of the high plasticizer content layer to the low plasticizer content layer is 1 / (3-5); more preferably, the thickness ratio of the high plasticizer content layer to the low plasticizer content layer of the double-layer PVB film is 1 / 5, minimizing the thickness of the high plasticizer content layer and ensuring the overall strength of the double-layer PVB film.

[0021] Preferably, the first conductive film and the second conductive film are conductive films formed by sputtering a transparent indium tin oxide (ITO) conductive layer onto a PET microfilm using magnetron sputtering technology. The thickness of the PET microfilm is 25-50 μm, and the thickness of the indium tin oxide (ITO) is 50-100 nm.

[0022] More preferably, the sheet resistance of the first conductive film and the second conductive film is ≤150Ω / □; and the light transmittance is >85%.

[0023] Optical UV adhesive is used for bonding PVB and PET, offering high optical transparency and clarity, and becoming almost completely transparent after curing. No high temperature is required during bonding, avoiding the damage to the ITO layer caused by thermal shrinkage and curling when using hot melt adhesive to laminate the ITO-PET conductive film and PVB film. When the laminated dimming film is pressed into the interlayer glass, the optical UV adhesive cures and provides thermal stability, preventing thermal slippage and misalignment.

[0024] Transparent epoxy resin AB adhesive is a two-component adhesive composed of epoxy resin and an amine curing agent. It has low viscosity and gradually cures over time. After curing, it is colorless and transparent with excellent temperature resistance. When bonding PVB / PET, initial bonding occurs under roller tension, followed by 24 hours of curing after roll-up to ensure a smooth bond and avoid damage to the ITO layer of the conductive film.

[0025] Preferably, the polymer-dispersed liquid crystal layer is obtained by coating a nematic liquid crystal dispersion. The nematic liquid crystal dispersion is either a commercially available UV-curable liquid crystal dispersion or a self-prepared UV-curable liquid crystal dispersion.

[0026] More preferably, the nematic liquid crystal dispersion has the following weight composition: 70-78 parts optical UV adhesive and 25-30 parts nematic liquid crystal. Specifically, the optical UV adhesive is selected from G41288 high-transparency UV adhesive from GGLOBAL.

[0027] More preferably, the nematic liquid crystal dispersion comprises, by weight: 65-70 parts acrylate monomer, 25-30 parts nematic liquid crystal, 5-8 parts crosslinking agent, and 1-1.5 parts photoinitiator. The acrylate monomer is two or more of the following: hydroxyethyl methacrylate, aromatic polyurethane acrylate, lauryl methacrylate, and butyl acrylate. The crosslinking agent is one of polyethylene glycol diacrylate and 1,4-butanediol diacrylate. The photoinitiator is at least one of ITX, TPO, 2959, and 651.

[0028] Preferably, the refractive index anisotropy range Δn of the nematic liquid crystal is 0.18-0.25, and the clearing point is ≥90℃.

[0029] More preferably, depending on the light-shielding and heat-insulating requirements of the dimming film, one of nano-carbon black, nano-titanium nitride, or nano-cesium tungstate can be doped into the liquid crystal dispersion.

[0030] This invention provides a method for preparing a polyvinyl butyral-based dimming film, the specific preparation steps of which are as follows:

[0031] (1) High-plasticizer PVB material and low-plasticizer PVB material were prepared according to the formula, and then melt-extruded separately into two extruders. After being cast through a precision T-die, the materials were stacked and bonded, and then rapidly cooled and shaped by a quenching roller to obtain a double-layer PVB film.

[0032] (2) Prepare the liquid crystal dispersion according to the weight parts and store it at low temperature in the dark;

[0033] (3) On the roll-to-roll production line, the double-layer PVB film is unwound and treated by a corona device to achieve a dyne value of 40-45mN / m on the side with low plasticizer content. The adhesive is then coated onto the corona-treated side by continuous roller coating. The PET-ITO conductive film is unwound and treated by a corona device to achieve a dyne value of 45-50mN / m on the PET side. It is then continuously bonded with the adhesive coating layer, pressed by tension rollers, and cured to obtain a composite conductive film.

[0034] (4) Take the composite conductive film out from the unwinding shaft, coat the liquid crystal dispersion on the ITO side through the slit coating head; simultaneously unwind another roll of composite conductive film, the ITO side and the liquid crystal dispersion coating layer are continuously bonded, the air bubbles are removed by the flexible roller, UV continuous curing, and then the film is wound up to obtain a polyvinyl butyral-based dimming film.

[0035] Preferably, the double-layer PVB film in step (3) is dried to a moisture content of ≤0.2% before use.

[0036] Preferably, the tension of the tension roller pressing in step (3) is 3-5 N / cm. Appropriate tension ensures that the PVB film and the conductive film are tightly bonded, while excessive tension will cause the conductive film to deform and warp.

[0037] Preferably, the UV curing in step (4) uses continuous irradiation with a 365 nm ultraviolet light source, with an irradiation intensity of 100-300 mW / cm². 2 The irradiation time is 10-30 seconds.

[0038] Compared with the prior art, the beneficial effects of the present invention are:

[0039] 1. This invention relates to a polyvinyl butyral (PVB)-based dimming film. The PVB film, with its double-layer structure and varying plasticizer content, serves as both the outer bonding and support substrate. When laminated with sandwich glass, the high-plasticizer-content PVB film exhibits good flexibility and easy heat-melting flow, allowing direct contact with the glass. Pressure can be applied at lower temperatures to achieve sufficient flow and tight adhesion to the glass, preventing bubble defects and avoiding damage to the liquid crystal layer during high-temperature pressing. The low-plasticizer layer of the PVB film is thermally stable, preventing slippage damage and effectively protecting the internal PDLC functional layer.

[0040] 2. This invention utilizes non-hot melt adhesives such as optical UV adhesive and epoxy resin AB adhesive to bond PVB / PET. The PVB film is pre-integrated with an ultra-thin ITO-PET conductive film, allowing the PDLC functional layer to be directly encapsulated between two electrode-bearing PVB films, forming an inseparable integral dimming film. When used in laminated glass, it eliminates the need for multiple layers of lamination, significantly simplifying the lamination process and fundamentally solving the problem of thermal melting, slippage, and misalignment of the PDLC film and PVB film when they are stacked separately in laminated glass.

[0041] 3. The polyvinyl butyral-based dimming film of this invention is produced in a roll-to-roll continuous industrial process with stable technology and no warping or deformation during layer lamination. It replaces the intermittent production process of single-sheet hot pressing in the laboratory, providing technical support for the stable mass production of dimming films for automotive and architectural glass. Attached Figure Description

[0042] Figure 1 This is a schematic diagram of the layer structure of a polyvinyl butyral-based dimming film.

[0043] Wherein: 1-first adhesive film, 2-second adhesive film; 3-first conductive film, 4-second conductive film, 5-PDLC functional layer; 101-first adhesive film high plasticizer content layer, 102-first adhesive film low plasticizer content layer, 201-second adhesive film high plasticizer content layer, 202-second adhesive film low plasticizer content layer, 301-first conductive film PET layer, 302-first conductive film ITO conductive layer, 401-second conductive film PET layer, 402-second conductive film ITO conductive layer. Detailed Implementation

[0044] The technical objectives, solutions, and effects of the invention are described in detail below through examples and specific application effect tests. Unless otherwise specified, all materials or process conditions described in the examples are conventional and understandable to those skilled in the art. Unless otherwise expressly stated, the terms "comprising" or "containing" in the specification do not exclude the addition of conventional materials or additives as required by convention. For example, in the preparation of a double-layer PVB film, while ensuring the formation of double-layer PVB films with different plasticizer contents, conventional additives such as ultraviolet absorbers and antioxidants may also be added during the preparation of the PVB film. Some supporting materials are:

[0045] PVB resin, hydroxyl content 20wt%; PVB resin, hydroxyl content 12wt%, self-made.

[0046] Maleic anhydride-grafted EVA: grade Orevac18211, melting temperature 75℃, Arkema, France.

[0047] The ITO-PET conductive film used is a magnetron sputtered conductive film with a sheet resistance ≤150Ω / □, a transmittance >85%, a PET thickness of 25μm, and an ITO thickness of 100nm.

[0048] Liquid crystal material: Nematic liquid crystal SLC1717 with biphenyl structure, Δn=0.20, clearing point 92℃, provided by Shijiazhuang Chengzhi Yonghua Liquid Crystal Co., Ltd.

[0049] Example 1

[0050] like Figure 1 As shown in the schematic diagram of the layer structure of the polyvinyl butyral-based dimming film of the present invention, from top to bottom, it includes a first adhesive film 1, a first conductive film 3, a PDLC functional layer 5, a second conductive film 4, and a second adhesive film 2; the first adhesive film 1 and the second adhesive film 2 are both double-layer PVB adhesive films; the first adhesive film 1 is composed of a first adhesive film high plasticizer content layer 101 and a first adhesive film low plasticizer content layer 102; the second adhesive film 2 is composed of a second adhesive film high plasticizer content layer 201 and a second adhesive film low plasticizer content layer 202; the first conductive film 3 and the second conductive film 4 are both PET-ITO conductive films; the first conductive film 3 is composed of a first conductive film PET layer 301 and a first conductive film ITO conductive layer 302; the second conductive film 4 is composed of a second conductive film PET layer 401 and a second conductive film ITO conductive layer 402.

[0051] The first low plasticizer content layer 102 of the first adhesive film 1 is bonded to the first conductive film PET layer 301 of the first conductive film 3 by optical UV adhesive; the second low plasticizer content layer 202 of the second adhesive film 2 is bonded to the second conductive film PET layer 401 of the second conductive film 4 by optical UV adhesive.

[0052] The preparation method of polyvinyl butyral-based dimming film is as follows:

[0053] (1) According to the formula, 100 kg of PVB resin (hydroxyl content 20 wt%), 22 kg of plasticizer triethylene glycol diisooctyl ester, 0.2 kg of antioxidant 245, and 0.3 kg of ultraviolet absorber UV-329 are stirred and dispersed evenly to obtain a low-plasticizer PVB material; 100 kg of PVB resin (hydroxyl content 12 wt%), 80 kg of plasticizer triethylene glycol diisooctyl ester, 8 kg of maleic anhydride-grafted EVA, 5 kg of epoxy resin E44, 0.2 kg of antioxidant 245, and 0.3 kg of ultraviolet absorber UV-329 are stirred and dispersed evenly to obtain a high-plasticizer PVB material; these are added to two extruders for melt extrusion, and the feeding speed of each is adjusted. After being cast through a precision T-die, the layers are superimposed and bonded, and then rapidly cooled and shaped by a quenching roller to obtain a double-layer PVB film with a thickness of 0.38 mm; the thickness ratio of the high-plasticizer content layer to the low-plasticizer content layer of the double-layer PVB film is adjusted to 1 / 5;

[0054] (2) Prepare a liquid crystal dispersion by mixing 70 parts by weight of optical UV adhesive (Glubon G41288) and 30 parts by weight of nematic liquid crystal SLC1717, and store it at low temperature and away from light.

[0055] (3) Dry the double-layer PVB film to a moisture content ≤0.2%. On the roll-to-roll production line, unwind the double-layer PVB film and treat it with a corona treatment device to achieve a dyne value of 45mN / m on the side with low plasticizer content. Apply optical UV adhesive (G41288) to the corona-treated side using continuous roller coating, with the coating thickness controlled within 10μm. Unwind the PET-ITO conductive film and treat it with a corona treatment device to achieve a dyne value of 50mN / m on the PET side. Continuously bond it with the optical UV adhesive coating layer, press it with a tension roller with a tension of 3N / cm, and irradiate it with a 365nm wavelength ultraviolet lamp with an irradiation intensity of 150mW / cm. 2 The film is cured by irradiation for 10 seconds, then rolled up to obtain a composite conductive film.

[0056] (4) Take the composite conductive film from the unwinding shaft, coat the ITO surface with liquid crystal dispersion through a slit coating head, and the coating thickness is 15μm; simultaneously unwind another roll of composite conductive film, with the ITO surface and the liquid crystal dispersion coating layer continuously bonded, remove air bubbles by a flexible roller, and continuously irradiate with a 365 nm ultraviolet light source at an irradiation intensity of 150mW / cm. 2 The irradiation time was 10s, and the film was wound up to obtain a polyvinyl butyral-based dimming film.

[0057] Example 2

[0058] 100 kg of PVB resin (hydroxyl content 12 wt%), 70 kg of plasticizer dibutyl fumarate, 12 kg of maleic anhydride-grafted EVA, 3 kg of epoxy resin E44, 0.2 kg of antioxidant 245, and 0.3 kg of ultraviolet absorber UV-329 were stirred and dispersed evenly to form a high plasticizer PVB material; the remaining processes and formulations were the same as in Implementation 1.

[0059] Example 3

[0060] (1) According to the formula, 100kg of PVB resin (hydroxyl content 20wt%), 30kg of plasticizer triethylene glycol diisooctyl ester, 0.2kg of antioxidant 245, and 0.3kg of ultraviolet absorber UV-329 are stirred and dispersed evenly to form a low plasticizer PVB material; 100kg of PVB resin (hydroxyl content 12wt%), 80kg of plasticizer triethylene glycol diisooctyl ester, 10kg of maleic anhydride grafted EVA, and 5kg of epoxy resin E44 are mixed and dispersed evenly to form a low plasticizer PVB material. 0.2 kg of antioxidant 245 and 0.3 kg of UV absorber UV-329 were stirred and dispersed evenly to form a high-plasticizer PVB material. These were then melt-extruded separately into two extruders, with the feed speeds adjusted. After being cast through a precision T-die and laminated, the layers were quickly cooled and shaped using quench rollers to obtain a 0.38 mm thick double-layer PVB film. The thickness ratio of the high-plasticizer content layer to the low-plasticizer content layer of the double-layer PVB film was controlled to 1 / 5.

[0061] (2) Prepare a liquid crystal dispersion by mixing 40 parts of aromatic polyurethane acrylate, 25 parts of butyl acrylate, 30 parts of nematic liquid crystal SLC1717, 5 parts of crosslinking agent polyethylene glycol diacrylate, and 1 part of photoinitiator 651 according to the weight parts, and store it at low temperature and away from light.

[0062] (3) Dry the double-layer PVB film to a moisture content of ≤0.2%. On the roll-to-roll production line, unwind the double-layer PVB film and treat it with a corona device to achieve a dyne value of 45mN / m on the side with low plasticizer content. Apply transparent epoxy resin AB glue (AB two-component glue, epoxy resin and amine curing agent ratio 1:1, viscosity 300cp) to the corona-treated side by continuous roller coating. Control the coating thickness to within 10μm. Unwind the PET-ITO conductive film and treat it with a corona device to achieve a dyne value of 50mN / m on the PET side. Continuously bond it with the epoxy resin AB glue coating layer. Press it with a tension roller with a tension of 3N / cm, roll it up, and cure it at 35℃ for 24h to obtain a composite conductive film.

[0063] (4) Take the composite conductive film from the unwinding shaft, coat the ITO surface with liquid crystal dispersion through a slit coating head, and the coating thickness is 15μm; simultaneously unwind another roll of composite conductive film, with the ITO surface and the liquid crystal dispersion coating layer continuously bonded, remove air bubbles by a flexible roller, and continuously irradiate with a 365 nm ultraviolet light source at an irradiation intensity of 150mW / cm. 2 The irradiation time was 15s, and the film was wound up to obtain a polyvinyl butyral-based dimming film.

[0064] Comparative Example 1

[0065] The PVB film did not employ a double-layer structure; instead, it was entirely composed of low-plasticizer PVB film. 100 kg of PVB resin (20 wt% hydroxyl content), 22 kg of plasticizer triethylene glycol diisooctanoate, 0.2 kg of antioxidant 245, and 0.3 kg of UV absorber UV-329 were stirred and dispersed evenly to form the low-plasticizer PVB material; a single-layer low-plasticizer PVB film with a thickness of 0.38 mm was then prepared. The remaining processes were identical to those in Example 1.

[0066] Comparative Example 2

[0067] When bonding the double-layer PVB adhesive film to the PET-ITO conductive film, a polyurethane hot melt adhesive layer is used, with a thickness of 10 μm. The film is then hot-pressed on a flatbed press at 100°C and 0.5 MPa for 30 seconds to obtain the composite conductive film. The remaining processing steps are the same as in Example 1.

[0068] Because of the significant difference in thermal shrinkage rates between PET and PVB, the composite conductive film is prone to warping after hot melt adhesive bonding due to the difference in cooling shrinkage, which affects the composite quality.

[0069] Comparative Example 3

[0070] 100 kg of PVB resin (hydroxyl content 12 wt%), 80 kg of plasticizer triethylene glycol diisooctanoate, 10 kg of epoxy resin E44, 0.2 kg of antioxidant 245, and 0.3 kg of ultraviolet absorber UV-329 were stirred and dispersed evenly to form a high plasticizer PVB material; the remaining processes and formulations were the same as in Example 1.

[0071] This comparative example does not use maleic anhydride-grafted EVA, but only adds epoxy resin to improve its adhesion to glass during glass interlayer lamination. Its fluidity with glass during low-temperature lamination is much lower than that of Example 1, and bubbles are present, but it is better than Comparative Example 1.

[0072] Comparative Example 4

[0073] 100 kg of PVB resin (hydroxyl content 12 wt%), 80 kg of plasticizer triethylene glycol diisooctanoate, 17 kg of maleic anhydride-grafted EVA (melting point 80℃), 0.2 kg of antioxidant 245, and 0.3 kg of ultraviolet absorber UV-329 were stirred and dispersed evenly to form a high plasticizer PVB material; the remaining processes and formulations were the same as in Example 1.

[0074] This comparative example does not use epoxy resin. By adding maleic anhydride-grafted EVA, the adhesion to glass during glass interlayer lamination is improved. It has good flow and filling properties with glass during low-temperature lamination, but the bonding strength with glass is affected.

[0075] Dimming film performance test:

[0076] Cut and sample the film, peel off electrodes from both sides of the dimming film, print silver paste, attach copper foil, and dry and cure to obtain a dimming test sample with electrode leads. Connect the electrodes to an adjustable low-voltage AC power supply of 0-85V, and determine the voltage at which the dimming film has the maximum light transmittance as the saturation voltage (approximately 67V). Referring to GB / T2410-2008 "Determination of Light Transmittance and Haze of Transparent Plastics", use a spectrophotometer to measure the light transmittance and haze of the dimming film when powered on (67V) and when powered off. Observe the defects of the dimming film when powered on. See Table 1.

[0077] Table 1: Performance of Dimming Film

[0078]

[0079] By conducting a lighting test on the sample, the dimming film obtained by this invention has a transmittance of >80% in the powered state and a haze of >95% in the de-powered state, demonstrating good dimming performance and meeting automotive-grade requirements.

[0080] Comparative Example 2 uses hot melt adhesive to bond PET and PVB. Due to the significant difference in heat shrinkage rate, after the hot melt adhesive is bonded, the composite conductive film is prone to warping due to the difference in cooling shrinkage, which affects the composite quality.

[0081] The effect of encapsulating the dimming film in glass:

[0082] After the dimming film was treated as electrode leads, it was sandwiched between two 2mm thick automotive-grade glass sheets in the lamination section and pressed together at 100℃ and 0.2MPa for 10 minutes to obtain dimming glass for testing. The dimming glass was also pressed together at 130℃ and 0.2MPa for 10 minutes to obtain dimming glass for testing. The haze of the dimming glass in the on / off state was tested at 67V. Defects such as bubbles, spots, fogging, and adhesion to the glass were observed after pressing. The technical requirements are: haze ≤5% when powered on and ≥95% when powered off. Test data are shown in Table 2.

[0083] Referring to T / TTPVB 0001-2020 "Polyvinyl butyral (PVB) film for automotive laminated glass", the peel strength of the PVB film at 180° interface with the glass after lamination was measured using a peel tester. The test data are shown in Table 2.

[0084] Table 2: Encapsulation effect of dimming film in glass

[0085]

[0086] Based on the above test results, when the dimming film is encapsulated in the laminated glass, the PVB film melts completely during high-temperature pressing at 130℃, which can increase the adhesion to the glass. However, the high temperature (exceeding the clearing point of the liquid crystal material) will cause the polymer-dispersed liquid crystal network to become unstable, resulting in reduced haze and fogging spots in the off-state.

[0087] This invention involves laminating a dimming film onto laminated glass. During lamination at a relatively low temperature (100°C), the high plasticizer content layer of the PVB film directly contacts the glass, allowing it to flow fully and bond tightly to the glass under pressure. This results in precise encapsulation, free of bubbles and interlayer slippage, and the bonding strength meets standard requirements. Simultaneously, the low-temperature lamination avoids damage to the liquid crystal caused by high temperatures.

[0088] The PVB film in Comparative Example 1 is a completely low-plasticizer PVB film. It has poor fluidity at 100°C, cannot fully bond with the glass interface, has many bubble defects, low bonding strength, and high haze when energized.

[0089] Comparative Example 2 uses hot melt adhesive to bond PET and PVB. When the composite dimming film is pressed onto the laminated glass, even at a temperature of 100°C, the thermal flow of the hot melt adhesive causes the dimming film to slip and misalign, resulting in bubbles and affecting the quality of the assembled product.

[0090] Comparative Example 3 did not use maleic anhydride-grafted EVA in the glass adhesive layer. During the hot pressing of the glass interlayer, the fluidity of the glass adhesive layer was slightly worse than that of Example 1, and there were more bubbles, but it was better than Comparative Example 1.

[0091] Comparative Example 4 did not use epoxy resin in the glass bonding layer. During the hot pressing of the glass interlayer, the glass bonding layer had good fluidity and no interface defects, but the peel strength was low.

[0092] Furthermore, the polyvinyl butyral-based dimming film of this invention uses a double-layer PVB film with different plasticizer contents as the outer bonding and carrier substrate to prepare the polyvinyl butyral-based dimming film. The high plasticizer content layer of the double-layer PVB film, combined with maleic anhydride-grafted EVA and epoxy resin, allows the high plasticizer content layer of the PVB film to directly contact the glass during lamination. This allows for sufficient flow and tight bonding with the glass under pressure at 100°C, preventing bubble formation and avoiding damage to the liquid crystal layer during high-temperature pressing. The use of non-hot melt adhesives such as optical UV adhesive and epoxy AB adhesive to bond PVB / PET fundamentally solves the problem of hot-melt slippage and misalignment of PDLC and PVB films when individually laminated in laminated glass. This technology is suitable for the stable mass production of dimming films for automotive and architectural glass.

[0093] This invention is not limited to the detailed preparation process described above. Under the premise of understanding the technical concept of this invention, any equivalent substitution of the raw materials of this invention by those skilled in the art falls within the protection and disclosure scope of this invention.

Claims

1. A polyvinyl butyral-based dimming film, characterized in that, The dimming film comprises, from top to bottom, a first adhesive film, a first conductive film, a PDLC functional layer, a second conductive film, and a second adhesive film; Both the first and second films are double-layer PVB films, which consist of a high-plasticizer content layer and a low-plasticizer content layer. The low-plasticizer content layer contains 20-30 wt% plasticizer of PVB resin, while the high-plasticizer content layer contains 60-80 wt% plasticizer of PVB resin. The high-plasticizer content layer contains maleic anhydride-grafted EVA and epoxy resin. Both the first conductive film and the second conductive film are PET-ITO conductive films; The low plasticizer content layer of the first adhesive film is bonded to the PET layer of the first conductive film by an adhesive; the low plasticizer content layer of the second adhesive film is bonded to the PET layer of the second conductive film by an adhesive. The adhesive used is either optical UV adhesive or transparent epoxy resin AB adhesive; The PDLC functional layer is a polymer-dispersed liquid crystal layer with a thickness of 10-20 μm.

2. The polyvinyl butyral-based dimming film according to claim 1, characterized in that, The low plasticizer content layer of the double-layer PVB film uses PVB resin with a hydroxyl content of 18-20 wt%; the high plasticizer content layer uses PVB resin with a hydroxyl content of 12-15 wt%.

3. The polyvinyl butyral-based dimming film according to claim 1, characterized in that, The plasticizer is either dibutyl fumarate or triethylene glycol diisooctanoate.

4. The polyvinyl butyral-based dimming film according to claim 1, characterized in that, The high plasticizer content layer contains maleic anhydride-grafted EVA with a melting point of 70-90℃, with a content of 8-12wt% of PVB resin; and contains epoxy resin, with a content of 3-5wt% of PVB resin.

5. The polyvinyl butyral-based dimming film according to claim 1, characterized in that, The thickness of the double-layer PVB film is 0.38 mm, and the thickness ratio of the high plasticizer content layer to the low plasticizer content layer is 1 / (3-5).

6. The polyvinyl butyral-based dimming film according to claim 1, characterized in that, The first conductive film and the second conductive film are conductive films formed by sputtering a transparent indium tin oxide conductive layer on a PET microfilm using magnetron sputtering technology. The thickness of the PET microfilm is 25-50 μm, and the thickness of the indium tin oxide conductive layer is 50-100 nm.

7. The polyvinyl butyral-based dimming film according to claim 1, characterized in that, The sheet resistance of the first conductive film and the second conductive film is ≤150Ω / □, and the light transmittance is >85%.

8. The polyvinyl butyral-based dimming film according to claim 1, characterized in that, The polymer-dispersed liquid crystal layer is obtained by coating a nematic liquid crystal dispersion; the nematic liquid crystal dispersion is selected from commercially available UV-curable liquid crystal dispersions or self-prepared UV-curable liquid crystal dispersions; the refractive index anisotropy range Δn of the nematic liquid crystal is 0.18-0.25, and the clearing point is ≥90℃.

9. A method for preparing a polyvinyl butyral-based dimming film according to any one of claims 1-8, characterized in that, The specific preparation steps are as follows: (1) According to the formula, high plasticizer PVB material and low plasticizer PVB material are prepared and added to two extruders for melt extrusion. After being cast out of the die lip through a precision T-die, they are superimposed and bonded. Then, they are rapidly cooled and shaped by a rapid cooling roller to obtain a double-layer PVB film. ​​ (2) Prepare the liquid crystal dispersion according to the weight parts and store it at low temperature in the dark; (3) On the roll-to-roll production line, the double-layer PVB film is unwound and treated by a corona device to achieve a dyne value of 40-45mN / m on the side with low plasticizer content. The adhesive is then coated onto the corona-treated side by continuous roller coating. The PET-ITO conductive film is unwound and treated by a corona device to achieve a dyne value of 45-50mN / m on the PET side. It is then continuously bonded with the adhesive coating layer, pressed by tension rollers, and cured to obtain a composite conductive film. (4) Take the composite conductive film out from the unwinding shaft, coat the liquid crystal dispersion on the ITO side through the slit coating head; simultaneously unwind another roll of composite conductive film, the ITO side and the liquid crystal dispersion coating layer are continuously bonded, the air bubbles are removed by the flexible roller, UV continuous curing, and then the film is wound up to obtain a polyvinyl butyral-based dimming film.

10. The method for preparing the polyvinyl butyral-based dimming film according to claim 9, characterized in that, In step (3), the tension of the tension roller pressing is 3-5 N / cm.

Citation Information

Patent Citations

  • Polymer disperse dye liquid crystal materials, electrochromic color-changing thin films and their preparation methods

    CN112379546B

  • Dimming components, their manufacturing methods, and vehicles

    CN115257116B

  • Intelligent dynamic dimming laminated glass and preparation method thereof

    CN115816941B